Research on the Parallel Operation of Micro-grid Multiple Inverters Based on Droop Control - GAO Shoucong; GU Housheng (Kongzhi Yu Xinxi Jishu)
Parallel operation of multiple inverters can effectively improve the capacity of micro-grid system and energy efficiency of renewable energy generation. In this paper, the operation principle of synchronous generator is used for reference, and the flexible interconnection of multiple inverters is carried out by using droop control, which can realize the active power distribution of multiple inverters in parallel operation without interconnection communication, meeting the plug and play of inverters. This paper introduced a design method of voltage and current dual loop controller, and analyzed the relationship between the control parameters and the response. For the problem of the resistance characteristics of low voltage micro-grid, virtual impedance is designed to meet the inductance requirements of droop control, which can enhance the power sharing effect of parallel inverters. The influence of key parameters on system stability was analyzed by means of eigenvalue method, and the correlation was verified by numerical simulation. Finally, a physical experiment platform was built and the effectiveness of the proposed control was verified.